2019
DOI: 10.1111/cico.12470
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Cycling for all? Race and Gender–Based Bicycling Inequalities in Portland, Oregon

Abstract: Amidst findings of increased bicycling in the United States, research continues to demonstrate that women and racial minorities are underrepresented as cyclists in the United States (Buehler and Pucher 2012). While quantitative data may reveal estimates of these disparities, we know little about the motivations or deterrents related to cycling as they are experienced by individuals. This article draws from 30 in–depth interviews with women and people of color in Portland, Oregon to clarify ongoing barriers to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 31 publications
1
13
0
Order By: Relevance
“…Together, these results demonstrate dramatically different effects of the Covid-19 pandemic on the travel behavior of different groups of riders. Some of these echo extant findings in the literature, like the differential experiences of harassment and threat faced by women and people of color while traveling in public spaces (Loukaitou-Sideris, 2014;Lubitow et al, 2019). But others are more novel, including the effects of service changes on different groups.…”
Section: Resultsmentioning
confidence: 70%
“…Together, these results demonstrate dramatically different effects of the Covid-19 pandemic on the travel behavior of different groups of riders. Some of these echo extant findings in the literature, like the differential experiences of harassment and threat faced by women and people of color while traveling in public spaces (Loukaitou-Sideris, 2014;Lubitow et al, 2019). But others are more novel, including the effects of service changes on different groups.…”
Section: Resultsmentioning
confidence: 70%
“…Research on abolitionism and movements to defund the police have been increasing in research years [125][126][127][128][129], bringing greater awareness to systemic issues of racism, classism, and gender-based discrimination in policing [130][131][132], while challenging dominant ideas that traffic safety is impossible without the police [133]. For example, a significant body of literature documents how police traffic stops enforce racial profiling and disproportionately target people of color and low-income commuters [134][135][136][137], including cyclists [138,139]. Robyn Maynard explains that in Canada and the United States, "policing emerged as and remains a form of racial, gendered and economic violence shaped by the logics of slavery and settler colonialism" [128].…”
Section: Discussion and Areas For Future Researchmentioning
confidence: 99%
“…In addition to negotiating their presence in the public space, women using micromobility also face the potential negative consequences of increased visibility while riding. Increased visibility is perceived to intensify harassment against women, and the same is stated when gender intersects with other identities, such as race (Balkmar, 2018;Lubitow et al, 2019;Ravensbergen, 2022). Having to deal with increased visibility and the prospect of harassment has a direct effect on the spatial behaviour of women using micromobility, as they develop specific strategies such as avoiding isolated or low-density urban spaces during night-time hours (Pellicer-Chenoll et al, 2021;Sersli et al, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…For instance, most parents acknowledge changing their behaviour when carrying children on their bicycles by riding more slowly or avoiding busy roads (Hatfield et al, 2019). Likewise, people of colour reported that concerns about police violence and unfair law enforcement treatment constrain their route schedules and choices (Lubitow et al, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation